2017
DOI: 10.1111/jeu.12410
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Spore Wall Protein from Antonospora locustae (Microsporidia: Nosematidae) Contributes to Sporulation

Abstract: Microsporidia are obligate intracellular parasites, existing in a wide variety of animal hosts. Here, we reported Aloc SWP2, a novel protein identified from the spore wall of Antonospora locustae (formerly, Nosema locustae, and synonym, Paranosema locustae), containing four cysteines that are conserved among the homologues of several Microspodian pathogens in insects and mammals. Aloc SWP2 was detected in the wall of mature spores via indirect immunofluorescence assay. In addition, immunocytochemistry localiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 52 publications
(95 reference statements)
0
13
0
Order By: Relevance
“…With the availability of genome data for the Encephalitozoonidae as well as many other microsporidia on MicrosporidiadB.org (part of EuPathdB.org) homologs of these SWPs have been found in most of the Encephalitozoonidae as well as in the other microsporidia genomes found on MicrosporidiadB (such as microsporidia that infect invertebrates) . Examples of such homologs include, Antonospora locustae SWP2 (AlocSWP2) and Enterocytozoon hepatopenaei SWP1 (EHSWP1) (Chen et al, 2017;Jaroenlak et al, 2018).…”
Section: Spore Wall Proteins (Swps)mentioning
confidence: 99%
See 1 more Smart Citation
“…With the availability of genome data for the Encephalitozoonidae as well as many other microsporidia on MicrosporidiadB.org (part of EuPathdB.org) homologs of these SWPs have been found in most of the Encephalitozoonidae as well as in the other microsporidia genomes found on MicrosporidiadB (such as microsporidia that infect invertebrates) . Examples of such homologs include, Antonospora locustae SWP2 (AlocSWP2) and Enterocytozoon hepatopenaei SWP1 (EHSWP1) (Chen et al, 2017;Jaroenlak et al, 2018).…”
Section: Spore Wall Proteins (Swps)mentioning
confidence: 99%
“…Spore wall proteins SWPs probably play a crucial role during the interaction of microsporidia and host cells (Southern et al, 2007). Several SWPs which can interact with host cells by binding to the heparin-binding motif (HBM) and host cell surface sulfated glycosaminoglycans (GAGs) have been identified from Nosema bombycis, Encephalitozoon spp., and Antonospora locustae (Hayman et al, 2001;Hayman et al, 2005;Southern et al, 2007;Li et al, 2009;Wu et al, 2009;Chen et al, 2017). Besides the interaction of HBM with GAGs during spore adherence to host cells, a separate study reported that host cell integrin is also involved in E. intestinalis adherence and infection of its host cells (Leonard and Hayman, 2017).…”
Section: Microsporidia Invasionmentioning
confidence: 99%
“…The stocks of A. locustae spores used in the experiments were routinely maintained in the Key Laboratory of Biological Control, Ministry of Agriculture, China Agricultural University. To isolate genomic DNA from the parasite, the spores were propagated in vivo by infecting its natural host, Locusta migratoria, which were routinely maintained in the same laboratory, following procedures described previously [32].…”
Section: A Locustae Sample Preparation and Dna Isolationmentioning
confidence: 99%
“…A. locustae showed great potential during the locust disaster that broke out at the end of last year, in particular. However, few studies have been carried out on the molecular infection mechanism of A. locustae [32]. Such research would be helpful for improving the application of microsporidia as bio-insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…These include NbSWP5, NbSWP11, NbSWP12, NbSWP16, NbSWP25 and NbSWP26 from N. bombycis [ 22 27 ], EcEnP1, EcEnP2 and chitin deacetylase (EcCDA) from E. cuniculi [ 28 , 29 ], and EiEnP1 from E. intestinalis [ 18 ]. Recently, Antonospora locustae SWP2 (AlocSWP2) has been shown to be involved in sporulation [ 30 ].…”
Section: Introductionmentioning
confidence: 99%